2020
DOI: 10.3389/fneur.2020.601898
|View full text |Cite
|
Sign up to set email alerts
|

Active Video Games and Low-Cost Virtual Reality: An Ideal Therapeutic Modality for Children With Physical Disabilities During a Global Pandemic

Abstract: Current guidelines against spread of coronavirus (COVID-19) interrupt non-essential rehabilitation services. Thus, individuals with physical disabilities such as children with cerebral palsy can no longer benefit from physical rehabilitation during this undetermined period. Using either a synchronous or asynchronous format, in collaboration with a therapist via telerehabilitation, we suggest that active video games and low-cost virtual reality are a promising delivery mode for at-home rehabilitation in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 71 publications
0
28
0
1
Order By: Relevance
“…Growing evidence supports active video games and low-cost virtual reality as viable therapeutic interventions for children with physical disabilities. These technologies are especially well-accepted by pediatric populations for the ludic and motivating features that lend themselves to nearly seamless incorporation into telerehabilitation ( 21 ). Mobile Based Rehabilitation (MBR) offers many advantages: social distancing can be maintained by the indirect interaction/digital interaction of patient and therapist, easy and cost-effective method, reduces the travel costs and time consumption, convenient to access at any time, and entertaining method of rehabilitation, using games and virtual environments improves participation.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence supports active video games and low-cost virtual reality as viable therapeutic interventions for children with physical disabilities. These technologies are especially well-accepted by pediatric populations for the ludic and motivating features that lend themselves to nearly seamless incorporation into telerehabilitation ( 21 ). Mobile Based Rehabilitation (MBR) offers many advantages: social distancing can be maintained by the indirect interaction/digital interaction of patient and therapist, easy and cost-effective method, reduces the travel costs and time consumption, convenient to access at any time, and entertaining method of rehabilitation, using games and virtual environments improves participation.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in the United Kingdom with 1521 adults aimed at examining the impact of the lockdown period on motivational factors for physical activity, identified that if the adults were motivated enough it would have been possible for them to have maintained or increased their levels of physical activity during lockdown [45]. Therefore, it is relevant that in addition to promoting physical activity in the pursuit of maintaining active behavior, activities that provide greater mental well-being, such as games and dancing, are also encouraged [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were 69% of respondents felt they better understand how to wash their hands properly after seeing this AR application. Another study [11] is a study that focuses on research on the use of VR for children with special needs (ABK) when they have to do rehabilitation at home during the COVID-19 pandemic. This study found that VR technology can be used in children with special needs to maintain and improve their motor function levels during home care.…”
Section: Related Workmentioning
confidence: 99%